2010
DOI: 10.2147/ijn.s12162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnetic nanoparticles of Fe3O4 on immune function in normal ICR mice

Abstract: Abstract:We investigated the effect of magnetic nanoparticles of Fe 3 O 4 (Fe 3 O 4 -MNPs) on the mice immune system. Imprinting control region (ICR) mice were assigned randomly into four groups and treated with normal saline or low, medium, or high doses of Fe 3 O 4 -MNPs, respectively. After intravenous administration of Fe 3 O 4 -MNPs for 72 hours, the peripheral T cells and the induction of primary immune responses in mice were investigated by flow cytometry and determined using enzyme-linked immunosorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 16 publications
1
42
0
Order By: Relevance
“…135 Further, SPIONs can alter immune function in a dose-dependent manner, as described by Chen et al in an imprinting control region mouse model. 10 In a study conducted by Mahmoudi et al, the main reason found for SPION-induced toxicity was formation of gas vesicles as a result of local alteration in ionic equilibrium and protein function. Mahmoudi et al developed a modified method for assessing cytotoxicity associated with SPIONs to establish a better correlation between in vitro and in vivo studies.…”
Section: Toxicity Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…135 Further, SPIONs can alter immune function in a dose-dependent manner, as described by Chen et al in an imprinting control region mouse model. 10 In a study conducted by Mahmoudi et al, the main reason found for SPION-induced toxicity was formation of gas vesicles as a result of local alteration in ionic equilibrium and protein function. Mahmoudi et al developed a modified method for assessing cytotoxicity associated with SPIONs to establish a better correlation between in vitro and in vivo studies.…”
Section: Toxicity Considerationsmentioning
confidence: 99%
“…Much research has been carried out to evaluate the biocompatibility of these magnetic nanoparticles and their possible adverse interactions with cellular and subcellular structures. 9,10 In this review, we discuss their desirable characteristics, including shape, hydrodynamic volume, surface charge and colloidal stability, various methods used for preparation of these nanoparticles, and their role in the biomedical sciences. Furthermore, limitations of SPIONs as drug delivery agents and their toxicity are discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Although iron oxide nanoparticles have been reported to affect the functionality of T cells and antigen-presenting cells, [12][13][14][15][16]18,19,23,24 evidence pertaining to their effects on Th1 cell-mediated immunity in vivo remains mostly unknown. It was previously reported that systemic administration of ovalbumin-sensitized mice with iron oxide nanoparticles suppresses, the serum production of ovalbumin-specific immunoglobulin G1 and immunoglobulin G2a, and the expression of both IFN-γ and IL-4 by splenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Oral and intravenous administrations of iron oxide nanoparticles alter T cell cellularity in normal nonsensitized mice. 16,17 It has been reported that serum levels of interleukin-2 (IL-2), IL-10, and interferon-γ (IFN-γ) are elevated in mice intravenously administered with iron oxide nanoparticles. 16 Moreover, it was recently reported that exposure to iron oxide nano particles suppresses humoral immunity and influences antigenspecific T cell reactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation